Esverdeando a cadeia de suprimentos: algumas evidências de empresas localizadas no Brasil - Jabbour, Ana Beatriz Lopes De Sousa [UNESP]; Azevedo, Fernanda De Souza [UNESP]; Arantes, Ariana Fernandes [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (Universidade Federal de São Carlos, 2013)
The purpose of this article is to identify and analyze how Green Supply Chain Management (GSCM) practices have been adopted by high-tech companies located in Brazil in order to create guidelines to support similar companies to incorporate GSCM initiatives. This research was based on case studies carried out in some representative companies in this sector. The main results are: (a) the supply chain structure can affect both the adoption of GSCM practices and the way they are adopted, (b) the Brazilian environmental legislation and international policies are very important to boost the adoption of GSCM practices, and (c) based on the results obtained, for each one of the six GSCM practices, suggestions for a more appropriate adoption are offered to similar companies.

O objetivo deste artigo é identificar e analisar como práticas de Green Supply Chain Management (GSCM) estão sendo adotadas por empresas de alta tecnologia localizadas no Brasil, a fim de gerar diretrizes de como empresas similares podem proceder para incorporar iniciativas de GSCM. A pesquisa foi desenvolvida a partir de estudo de casos com empresas representativas desse setor. Como principais resultados, destacam-se: (a) a estrutura da cadeia de suprimentos pode afetar a adoção e a forma como se adotam práticas de GSCM; (b) a legislação ambiental brasileira e as diretivas internacionais são muito importantes para impulsionar a adoção de práticas de GSCM; e (c) para cada uma das seis práticas de GSCM, apresentam-se sugestões de como empresas similares podem adotá-las com maior êxito.
Greening the supply chain: evidences of firms in Brazil
Keywords: Sustentabilidade; Green Supply Chain Management; Implementação de práticas; Setor de alta tecnologia; Brasil; Sustainability; Green Supply Chain Management; Implementation of practices; High technology sector; Brazil